Advances and challenges in men's health: a literature review (Research, Society and Development, 2023)
Introduction: Health is everyone's right and the state's duty, and to ensure this right, the SUS was created, where the UBS constitutes a gateway to health services. Men are included in this context, who for various reasons are negligent in relation to health, an action that increases male mortality data. Thus, the Ministry of Health launched the National Policy for Integral Attention to Men's Health, which aims to promote better health conditions for men. Methodology: The present study is a literature review, whose objective was to analyze the scientific publications from 2011-2022 about the advances and challenges faced in relation to men's health in Primary Care. Data collection was carried out by analyzing the databases: BDNEF, LILACS, and SCIELO, applying the descriptors: advances, challenges, men's health and nursing. Results and Discussion: The discrepancy in relation to the advances obtained, which are few, and challenges faced that appear in different ways, in this way nurses develop different strategies to rescue the male population, another strategy launched by the MS is the PNAISH, which tries to develop in the precarious health system that it is inserted. Conclusion: It is concluded, through the selected and analyzed articles, that men's health needs greater investments in public policies and actions that are aimed at men in their entirety, respecting their individualities and particularities, only then can we have changes in the negative situations and better quality of life for males.